(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Breast cancer is a malignancy of the cells in the breast tissue, which can originate from the glandular components (ductal epithelium or lobules) such as fat tissue, blood vessels and the nerves of the breast tissue . This community service activity is efforts to prevent breast cancer with Breast Self Examination (BSE), this activity was carried out at SMA Muhammadiyah I Palembang City by nursing lecturers, along with nursing students with a target of 28 students of SMA Muhammadiyah I Palembang. The community service team provides health education interventions about breast cancer and demonstrations on how to do BSE to students. This prevention effort shows that the average student knowledge score before being given the intervention was 38, the average student knowledge score after being given the intervention was 68 with a mean difference before and after being given the intervention of 30, which means this activity can increase students’ knowledge about cancer. breast and furthermore, it is hoped that it can reduce the incidence of breast cancer through early detection using BSE.